The efficacy of thoracoscopic fissureless lobectomy in patients with dense fissures - Igai, Hitoshi; Kamiyoshihara, Mitsuhiro; Yoshikawa, Ryohei; Osawa, Fumi; Kawatani, Natsuko; Ibe, Takashi; Shimizu, Kimihiro (Journal of Thoracic Disease; Vol 8, No 12 (December 31, 2016): Journal of Thoracic Disease, 2016)
Background: Prolonged air leakage after a lobectomy remains a frequent complication in patients with dense fissures. To avoid postoperative air leakage, we used the “thoracoscopic fissureless technique” for patients with dense fissures. A thoracoscopic approach is useful for the fissureless technique because it gives a good operative view from various angles without dividing the fissure. In this study, we compared the peri- or intraoperative results of thoracoscopic fissureless lobectomies to traditional lobectomies with fissure dissection for pulmonary artery (PA) exposure in order to identify the efficacy of thoracoscopic fissureless lobectomy. Methods: Between April 2012 and November 2015, 175 patients underwent a thoracoscopic lobectomy with three or four ports, of whom 14 underwent a fissureless lobectomy because of dense fissures. We compared the characteristics and perioperative outcomes of the patients who underwent the fissureless technique (fissureless technique group, n=14) and the traditional fissure dissection technique for PA exposure (traditional technique group, n=161). In our department, fissureless lobectomy is indicated for patients with a fused fissure (fissural grade III or IV as proposed by Craig in 1997) or inflammation makes it difficult to expose the PA, while the traditional technique is used for other patients. Results: Although the fissureless technique group had longer operation time than the traditional technique group (P=0.0045), there was no significant inter-group difference about blood loss (P=0.85), occurrence rate of intraoperative massive bleeding (P=0.6) or conversion rate to thoracotomy (P=0.31). According to postoperative results, there was no significant inter-group difference in duration of chest tube drainage (P=0.56), length of postoperative hospital stay (P=0.14), or morbidity rate (P=0.16). No mortality occurred in either group. Conclusions: A thoracoscopic fissureless lobectomy is feasible and safe, and useful to avoid postoperative air-leakage in patients with dense fissures.